Application of risk-based inspection using API 581 methodology to a pressure vessel in petrochemical plant - Mohd Khairul Hafiz, Khairuldin; Norhayati, Rosli; Abd Razak, Unazie Iskandar; Noryanti, Muhammad (AIP Publishing, 2024)
The pressure vessel in the processing plant is an important piece of equipment for the petrochemical plant. This equipment has been widely used in process plants for various operations, and all this equipment requires an inspection to prevent accident failures from happening. Nowadays, many companies adopted and used the risk-based inspection (RBI) methodology to manage an inspection at the equipment risk level. This study applied a method based on API 581 to a pressure vessel V −104 Condensate Drum, to provide the RBI risk ranking and a sufficient inspection plan for this equipment. Based on corrosion study analysis, there are two identified damage mechanisms which are internal thinning and external corrosion under insulation. Inspection data were collected during the last shutdown and the result of RBI analysis showed that the equipment has a “medium” risk category on the RBI date and a “medium-high” risk category on the RBI plan date. RBI analysis has recommended carrying out a visual inspection and ultrasonic thickness measurement to address the potential damage mechanism.